Introductory Speech - Collective Mobilisations in Africa and the Indian Ocean - Ramos, M. (P127 Collective Mobilisations in Africa and the Indian Ocean (CRG Africa in the Indian Ocean panel) - 6th European Conference of African Studies, 2015)
Panel organized by the AEGIS collaborative research group on Africa in the Indian Ocean. It will discuss ongoing research on the transnational and transoceanic trajectories of cultural and political movements, and the ways in which Indian Ocean networks have had an impact on history and development in Africa.